2005
DOI: 10.1086/429332
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Systemic Production of Prostaglandin E2in Children with Cerebral Malaria

Abstract: Prostaglandins (PGs) are important mediators of macrophage activity, vascular permeability, fever, erythropoiesis, and proinflammatory responses to infection. Our recent studies have shown that plasma levels of bicyclo-PGE2 (a stable end product of PGE2 metabolism) and leukocyte cyclooxygenase (COX)-2 gene expression are suppressed in children with malarial anemia. Since the role of PGs as immunomodulators of human cerebral malaria (CM) has not been examined, we investigated urinary levels of bicyclo-PGE2/crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
(57 reference statements)
2
23
0
2
Order By: Relevance
“…We have observed that these treatments increase CD8 + T cell function during P. yoelii infections, however a correlation of high levels of PGE 2 and COX-2 activation with low incidence of cerebral malaria has been established [69,70], suggesting that elevated PGE 2 may have an important beneficial effect for the host, despite its inhibitory effect on T cells.…”
Section: Discussionmentioning
confidence: 91%
“…We have observed that these treatments increase CD8 + T cell function during P. yoelii infections, however a correlation of high levels of PGE 2 and COX-2 activation with low incidence of cerebral malaria has been established [69,70], suggesting that elevated PGE 2 may have an important beneficial effect for the host, despite its inhibitory effect on T cells.…”
Section: Discussionmentioning
confidence: 91%
“…Africa is the continent with the highest incidence of malaria and, for example, in Uganda, the number of cases per 1000 individuals is as high as 478 (http://www.globalhealthfacts.org). Recent studies suggest that elevated plasma levels of PGE 2 in healthy children infected with malarial parasites may protect against severe clinical forms of malaria (Perkins et al, 2001(Perkins et al, , 2005. In humans, malaria is the most powerful known source of genetic selective pressure, and the frequency of polymorphic changes with malaria-protective effects is expected to be higher in affected populations (Kwiatkowski, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study of children with MA and/or hyperparasitemia showed that plasma bicyclo-PGE 2 levels and PBMC COX-2 gene expression are suppressed during acute malaria, with the lowest levels of COX-2 and PGE 2 associated with the most severe cases of disease [10]. It has also been shown that reduced urinary concentrations of bicyclo-PGE 2 are associated with adverse neurological sequelae and death among children with cerebral malaria [37], and that increasing pfHz deposition in cultured intervillous blood mononuclear cells obtained from women with placental malaria is correlated with decreased PGE 2 biosynthesis [38]. Additional studies performed in our laboratory confirmed that phagocytosis of pfHz by stimulated human PBMCs is responsible, at least in part, for decreased COX-2-derived PGE 2 biosynthesis during malaria [11].…”
Section: Discussionmentioning
confidence: 99%